Perancangan Kursi Kerja Di PT. Rezza Usaha Mandiri dengan Pertimbangan Anthropometri - Apandi; Amri Hidayat; Mietra Anggara; Aldrin Aldrin (Jurnal GEAR (Energi, Perancangan, Manufaktur & Material), 2023)
The design of this work chair aims to provide optimal comfort and posture support according to the user's anthropometric characteristics. In an effort to create chairs that fit the various dimensions of the human body, anthropometric and target population data were collected and analyzed carefully. The results of this anthropometric analysis become the basis for designing the right chair dimensions. This chair offers easy and intuitive adjustments, such as adjustable seat height, adjustable backrest, and adjustable arms, so that the chair conforms to the most comfortable posture position for the wearer. In addition, this work chair uses ergonomic, high-quality materials, with features such as molded foam to increase comfort and shock absorption. This chair is also designed with an attractive aesthetic appearance, creating a pleasant work environment and supporting productivity. Through this approach, the design of an anthropometry-based work chair is expected to improve user health and comfort, reduce the risk of injury related to wrong sitting position, and increase efficiency and productivity in the work environment. Keywords: Design, Work Chair, Modification